1997
DOI: 10.1128/jvi.71.1.527-538.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an abundant, unique 1.7-kilobase bovine herpesvirus 4 (BHV-4) late RNA and mapping of a BHV-4 IE2 transactivator-binding site in its promoter-regulatory region

Abstract: We characterized an abundant late 1.7-kb cytoplasmic polyadenylated RNA (L1.7 RNA) transcribed from the bovine herpesvirus 4 (BHV-4) HindIII W fragment, in a region of the genome not conserved with Epstein-Barr virus and herpesvirus saimiri. L1.7 RNA contains only extremely short (<100 nucleotides) open reading frames followed by two repeat arrays. The first repeat array contains 11 copies of a 23-bp unit, TGGCACTA GTAGCATTTAACCCC. The second and third copies are each interrupted by 15-to 17-bp sequences that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Bioinformatic studies revealed ENEs, thus indicating the presence of PAN RNAs, in four other γ-herpesviruses: retroperitoneal fibromatosis-associated herpesvirus Macaca nemestrina (RFHVMn), Rhesus macaque rhadinovirus (RRV), and equine herpesvirus 2 and 5 (EHV-2 and EHV-5) [ 8 ]. A fifth PAN RNA homolog lacking an ENE was identified as a highly abundant noncoding RNA expressed from a syntenic genomic locus of bovine herpesvirus 4 (BHV-4) [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic studies revealed ENEs, thus indicating the presence of PAN RNAs, in four other γ-herpesviruses: retroperitoneal fibromatosis-associated herpesvirus Macaca nemestrina (RFHVMn), Rhesus macaque rhadinovirus (RRV), and equine herpesvirus 2 and 5 (EHV-2 and EHV-5) [ 8 ]. A fifth PAN RNA homolog lacking an ENE was identified as a highly abundant noncoding RNA expressed from a syntenic genomic locus of bovine herpesvirus 4 (BHV-4) [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…U, uninfected. The probe was a 32 P-labelled cloned cDNA of BHV-4 L1.7 RNA (Bermudez-Cruz et al ., 1997 ). Circular (C) and linear (L) viral genomes are indicated. ).…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA prepared 24 h p.i. was assayed by Northern blot analysis for expression of representative early (BHV-4 homologue of herpes simplex virus 1 major DNA binding protein; Chang & van Santen, 1992 ) and late (L1.7; Bermudez-Cruz et al ., 1997 ) RNAs. Early RNA was detected in RD-4 cells at approximately one-fifth the level detected in BT cells (not shown).…”
Section: Resultsmentioning
confidence: 99%